Precoder Design for Simultaneous Wireless Information and Power Transfer with Finite-Alphabet Inputs - Xiaodong Zhu; Weiliang Zeng; Chengshan Xiao (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2017)
In this paper, we investigate the mutual information maximization for a multiple-input multiple-output (MIMO) system with simultaneous wireless information and power transfer (SWIPT), where perfect channel state information (CSI) is known at the transmitter. We formulate an optimization problem under the constraints of transmit power and harvested energy. Different from previous work, we assume the input signals to be taken from finite-alphabet inputs instead of Gaussian signals. The formulated problem is NP-hard, so a global optimal solution can not be found with polynomial time complexity. However, by exploiting the structure of the problem, this optimization problem can be transformed into a semidefinite programming (SDP) problem, and then a near optimal algorithm based on semidefinite relaxation (SDR) technique is developed. Simulation results show the efficacy of the proposed algorithm.